2019
DOI: 10.1136/bmjresp-2019-000456
|View full text |Cite
|
Sign up to set email alerts
|

CNS imaging studies in cystic fibrosis patients presenting with sudden neurological events

Abstract: BackgroundAcute neurological events may present as an extrapulmonary complication in patients with cystic fibrosis (CF). These events can be secondary to a range of different aetiologies.MethodsA retrospective analysis of 476 medical records of CF patients attending a large teaching hospital between 2000 and 2018 was performed. Patients presenting with acute neurological events who had MRI brain imaging were evaluated. Patients who had headaches without associated neurological symptoms were excluded from this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Infertility induced by the absence of vas deferens can be overcome by intracytoplasmic injection of sperm after transcutaneous harvesting the sperm from the epididymis [ 39 ]. Neurological examination proved to be particularly necessary in agitated patients, in exacerbation of chronic respiratory failure, in whom hypoxic, but especially hypercapnic cerebral distress, required the exclusion of an organic neurological pathology [ 40 ]. Endocrinological examination was practiced in most children, given the endocrine and metabolic manifestations of malabsorption syndrome.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Infertility induced by the absence of vas deferens can be overcome by intracytoplasmic injection of sperm after transcutaneous harvesting the sperm from the epididymis [ 39 ]. Neurological examination proved to be particularly necessary in agitated patients, in exacerbation of chronic respiratory failure, in whom hypoxic, but especially hypercapnic cerebral distress, required the exclusion of an organic neurological pathology [ 40 ]. Endocrinological examination was practiced in most children, given the endocrine and metabolic manifestations of malabsorption syndrome.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…As there is evidence of CFTR expression in human neuronal cells, CFTR modulator therapy may provide an additional benefit in terms of improvements in cognition where CFTR function is potentially important. We have recently reported CNS abnormalities in CF patients [16]. Furthermore, we have found that IVA and its metabolites have off-target effects on brain tissue [17].…”
Section: Introductionmentioning
confidence: 91%